THE INFLUENCE OF COMMUNICATION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT XPRESS PRINT TANGERANG CITY - kurniawan aryanto putra; Zackharia Rialmi (Jurnal Manajemen & Pendidikan [JUMANDIK], 2025)
The purpose of this research is to determine the effect of communication and work discipline on employee performance at Xpress Print Tangerang City. This type of research is a type of quantitative research using data collection techniques using observation, interviews, and questionnaires. The population in this research is Xpress Print employees in Tangerang City, namely 150 employees. The technique for determining the number of samples taken as respondents in the research This is by using the Slovin formula. The results of the Slovin formula calculation show a total of 60 employees. The data analysis techniques in this research are descriptive analysis, research instrument test, classical assumption test, multiple linear regression test, correlation coefficient test, coefficient of determination test, as well as t test and F test using SPSS version 26 tools. The results of this study show that There is an influence between Communication (X1) on Employee Performance (Y) at Xpress Print Tangerang City, this can be seen from the results of the t test with a value of tcount > ttable (12.743 > 2.00), this is also proven by the significance of 0.000 < 0.5 . Thus, Ho1 is rejected and Ha1 is accepted, then there is also an influence between Work Discipline (X2) on Employee Performance (Y) at Xpress Print Tangerang City, this can be seen from the results of the t test with a value of tcount > ttable (13.652 > 2.00) , this is also proven by the significance of 0.000 < 0.05, thus Ho2 is rejected and Ha2 is accepted, and thirdly there is an influence between Communication (X1) and Work Discipline (X2) on Employee Performance (Y) at Xpress Print Tangerang City, This can be seen from the results of the F test with a value of Fcount > Ftable or (123.039 > 3.15), this is also confirmed by Sig < 0.05 or (0.000 < 0.05), thus Ho3 is rejected and Ha3 is accepted.